Modeling Alzheimer's disease in progeria mice. An age-related concept. Issue 1 (1st January 2018) - Sharma, Kavita; Darvas, Martin; Keene, C. Dirk; Niedernhofer, Laura J.; Ladiges, Warren
ABSTRACT: The prevalence of Alzheimer's disease (AD) is expected to dramatically increase in older people worldwide. Efforts to find disease-modifying treatments have been largely unsuccessful because of the focus on disease-specific pathogenesis, and lack of animal models to study AD in the context of aging and age-related co-morbidities. The geroscience approach to studying AD would suggest that modulation of aging per se would be a useful strategy, but a mammalian model system that combines both aging and AD is not available. One approach to study old age and AD is to utilize murine models of progeroid syndrome, which can provide a number of advantages not only for basic aging biology but also for preclinical drug testing. A progeria background, such as the Ercc1 mutant mouse ( Ercc1 −/Δ ), provides an aging component not seen in current murine models of AD that lack age-related co-morbidities typical of AD patients. Ercc1 −/Δ mice experience the same types of stochastic endogenous DNA damage as WT mice, but accumulate lesions faster due to impaired DNA repair, which accelerates the normal aging process by 6-fold. These mice do not show frank AD pathology but represent a predisposed or hypersensitive environment for AD pathology, where pathogenic elements of AD can be introduced, either by crossing with well-established AD transgenic mouse lines, or transcranial stereotaxic delivery directly into the brain. Since Ercc1 −/Δ mice age five to six times faster than WT mice, very rapid characterization and testing of therapeutic interventions is possible. Studies are urgently needed to capitalize on the highly informative potential of this novel AD mouse model.